Positive electrode material and preparation method thereof, and alkaline secondary battery
By co-precipitating a tetravalent cobalt compound coating on the nickel hydroxide positive electrode material, the problem of insufficient conductivity and stability of the positive electrode material in the prior art is solved, and higher battery performance and high temperature stability are achieved.
Patent Information
- Application Number
- CN202211130721.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-16
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-09-16
AI Technical Summary
The conductivity, stability and uniformity of the existing alkaline secondary battery positive electrode materials lead to poor battery performance, especially at severe capacity attenuation at high temperatures.
The positive electrode material was prepared by co-precipitation method, the core material was nickel hydroxide, and the cladding layer contained no less than 45% by weight of tetravalent cobalt compound. The pH value of the solution was controlled and the addition of sodium hypochlorite solution was oxidized to form a cladding layer with a porous structure.
The conductivity and stability of the cathode material are significantly improved, the high temperature stability and capacity utilization of the battery are enhanced, and the capacity can be restored in a short circuit or overdischarge state.
Smart Images

Figure CN115498152B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of chemical battery materials, and in particular to a positive electrode material, a method for preparing the positive electrode material, and an alkaline secondary battery comprising the positive electrode material. Background Art
[0002] Alkaline secondary batteries include nickel-cadmium secondary batteries, nickel-zinc secondary batteries, and nickel-hydrogen secondary batteries. The positive electrode active material of alkaline secondary batteries is spherical nickel hydroxide. The performance of alkaline secondary batteries is largely affected by the positive electrode active material. However, nickel hydroxide powder is an electrical insulator (also known as a low-conductivity P-type semiconductor), and therefore lacks conductivity. There is a large contact resistance between nickel hydroxide particles and between nickel hydroxide and the current collector, which causes nickel hydroxide to be unable to fully react during the charge and discharge process, affecting the utilization rate of the positive electrode active material and the discharge capacity of the battery positive electrode.
[0003] In view of the above technical problems, the existing technical solutions include adding an appropriate amount of additives to nickel hydroxide to improve the performance of the positive electrode. For example, cobalt is dissolved in nickel hydroxide powder to improve the utilization rate at high temperature, or zinc or magnesium is dissolved in nickel hydroxide powder to improve the life characteristics. From the perspective of simultaneously improving the utilization rate, life characteristics and rate characteristics at high temperatures, it is effective to use cobalt or cobalt compounds (such as CoO, Co2O3, Co3O4, Co(OH)2, etc.) as additives. The added cobalt or cobalt compound is dissolved in a high concentration alkali metal hydroxide solution as an electrolyte of an alkaline secondary battery, and is oxidized during charging to form cobalt hydroxide oxide, and is coated on the surface of the nickel hydroxide particles, thereby embodying conductivity and forming a conductive network between the nickel hydroxide particles.
[0004] There are two main ways to add cobalt additives to the positive electrode of alkaline secondary batteries: physical doping and surface modification.
[0005] Among them, the physical doping method refers to directly mixing cobalt or cobalt compounds with nickel hydroxide to prepare positive electrode materials. Since nickel hydroxide and cobalt or cobalt compounds are both granular substances and the particle sizes are uneven, it is not easy to mix the particles of nickel hydroxide and cobalt or cobalt compounds evenly, resulting in uneven distribution of cobalt or cobalt compounds, and it is impossible to form a uniform conductive network on the surface of nickel hydroxide particles to effectively reduce the contact resistance between nickel hydroxide particles and between particles and current collectors. The utilization rate of active materials is low, and the electrode performance cannot be improved to a significant extent.
[0006] Among them, the surface modification method refers to uniformly coating a layer of metal cobalt or cobalt compound on the surface of spherical nickel hydroxide. There are two main existing coating methods: 1. Coating a cobalt film on the surface of spherical nickel hydroxide by chemical plating; 2. Co-precipitation coating Co(OH)2 on the surface of spherical nickel hydroxide. The method includes preparing an aqueous solution containing cobalt ions and an aqueous solution of caustic alkali, putting nickel hydroxide solid solution particles into an aqueous solution containing cobalt ions, and then slowly adding an aqueous solution of caustic alkali, and maintaining a constant pH value while stirring continuously. As a result, Co(OH)2 is precipitated on the surface of the nickel hydroxide solid solution particles, and then washed with water and vacuum dried to obtain nickel hydroxide solid solution particles coated with Co(OH)2.
[0007] However, the existing surface modification methods have the following technical problems:
[0008] 1. The operating conditions of the chemical plating method are very harsh and require the use of precious metals as catalysts;
[0009] 2. The coprecipitation method has harsh reaction conditions, such as the pH value and other conditions need to be strictly controlled. In addition, if the divalent cobalt compound coated on the surface of the spherical nickel hydroxide is not subsequently treated, since the divalent cobalt compound itself has no conductivity and is relatively soluble, it needs to be electrochemically oxidized to trivalent cobalt oxide (i.e., β-CoOOH) with effective conductive network function through the initial charging of the battery in order to conduct electricity. However, since the electrochemical oxidation reaction in the battery cannot completely convert the divalent cobalt oxide into trivalent cobalt oxide, the conductive performance of the conductive network is not perfect, and the utilization rate of the nickel hydroxide is not high;
[0010] 3. After the cobalt hydroxide is coated on the surface of the spherical nickel hydroxide by the coprecipitation method, the surface-coated cobalt hydroxide layer is oxidized into cobalt hydroxide oxide (β-CoOOH and / or γ-CoOOH) by a solid-gas oxidation reaction under high concentration alkaline solution and oxygen conditions. After the cobalt hydroxide oxide is coated on the surface of the spherical nickel hydroxide, the internal resistance of the nickel hydroxide electrode is reduced, and the positive electrode polarization is reduced, thereby improving the charging efficiency, discharge depth, and utilization rate of the active material of the electrode. However, this method has the following technical problems: (1) the spherical nickel hydroxide particles coated with cobalt hydroxide need to be physically mixed with an alkaline solution to form a slurry and then oxidized in an oxygen atmosphere, so there are problems of uneven oxidation and difficulty in accurately controlling the degree of oxidation when oxygen is used as an oxidant; (2) the fine particles will be bonded together to form larger spherical nickel hydroxide particle aggregates through the dissolution of Co(OH)2 on their surfaces and the redeposition of cobalt hydroxide oxide. In addition, the alkaline solution can also react with carbon dioxide in the air to form carbonates. The carbonates act as adhesives during the drying process of the spherical nickel hydroxide coated with cobalt hydroxide oxide, and will also cause some of the spherical nickel hydroxide fine particles to agglomerate. The agglomeration reduces the fluidity of the spherical nickel hydroxide particles coated with cobalt hydroxide oxide, making it difficult to fill them into the pores of the foamed nickel. The battery pole pieces produced are thick and brittle, and the battery is easily broken when it is wound, causing the battery to short-circuit, and it is impossible to assemble high-capacity batteries.
[0011] 4. After the cobalt hydroxide is coated on the surface of the spherical nickel hydroxide by the coprecipitation method, the cobalt hydroxide oxide is then coated on the surface of the spherical nickel hydroxide by mixing with an alkaline solution and a solution containing an oxidant. However, this method has the following technical problems: (1) The spherical nickel hydroxide particles coated with cobalt hydroxide oxide are unstable at high temperatures as the positive electrode of the battery. During the charge and discharge process at high temperatures, the coating layer of the particles is easily reduced to soluble Co(OH)2, leaving β-Ni(OH)2 exposed. However, β-Ni(OH)2 is more active in overcharging reaction at high temperatures and is easy to form an irreversible phase γ-NiOOH; (2) This method easily leads to uneven coating of nickel hydroxide; (3) When the nickel hydroxide coated with cobalt hydroxide is oxidized by a solution containing an oxidant, a part of the nickel hydroxide as the core material is also easily oxidized to generate relatively unstable nickel hydroxide oxide. Therefore, the adhesion of the cobalt hydroxide coating becomes unstable. Summary of the invention
[0012] In view of the technical problems existing in the prior art, the purpose of the present invention is to provide a positive electrode material, wherein the coating layer of the positive electrode material has excellent uniformity, conductivity and stability, and the positive electrode material is suitable as a positive electrode active material for an alkaline secondary battery.
[0013] In the first aspect, the present invention provides a positive electrode material, which includes a core material and a coating layer coated on the surface of the core material. The core material includes nickel hydroxide. The coating layer includes a tetravalent cobalt compound, and based on the weight of the coating layer, the content of the tetravalent cobalt compound is not less than 45wt%. The tetravalent cobalt compound in the coating layer has higher conductivity and is less likely to be reduced to +2-valent cobalt ions, because +2-valent cobalt ions are very easily soluble in alkaline solution, resulting in the destruction of the conductive network. Therefore, the alkaline secondary battery made of the positive electrode material provided by the present invention as the positive electrode active material has a higher capacity and a smaller internal pressure. Even if the alkaline secondary battery is over-discharged for a long time and placed in a short-circuit state, its capacity can be well restored by charging.
[0014] Furthermore, based on the weight of the positive electrode material, the cobalt content of the positive electrode material is preferably in the range of 2-10wt%. When the cobalt content of the positive electrode material is less than 2wt%, there are problems such as insufficient coating amount of the coating layer and poor coating effect; when the cobalt content of the positive electrode material exceeds 10wt%, the coating layer does not significantly improve the performance of the positive electrode material.
[0015] Furthermore, in order to improve the battery characteristics when used as the positive electrode of the battery, calcium (Ca), magnesium (Mg), zinc (Zn) and the like can be added as additive elements to the coating layer of the positive electrode material. However, when the cobalt content in the coating layer is less than 90wt%, the improvement in conductivity brought about by the coating cannot be fully obtained.
[0016] In one embodiment, in a coating layer of a positive electrode material provided by the present invention, the valence of cobalt in the cobalt compound other than the tetravalent cobalt compound is 3 or more, and good adhesion and conductivity can be obtained.
[0017] In one embodiment, the core material is of the general formula: Ni 1-x-y Co x N y Nickel hydroxide represented by (OH)2 (wherein x is 0.005-1, y is 0.005-1, and N is one of Ca, Mg, and Zn). The coating layer of the positive electrode material includes a tetravalent cobalt compound, and the content of the tetravalent cobalt compound is not less than 60wt% based on the weight of the coating layer.
[0018] Compared with the existing nickel hydroxide coated with γ-CoOOH and / or β-CoOOH, the positive electrode material provided by the present invention is more stable and has higher conductivity. The inventor unexpectedly found that the positive electrode material provided by the present invention as the positive electrode active material of the alkaline secondary battery can significantly inhibit the capacity decay problem of the alkaline secondary battery at high temperature. Although the specific principle is still unclear, the inventor speculates that the reasons include: (1) The coating layer with not less than 45wt% of the tetravalent cobalt compound expands the oxygen evolution potential (EOE ) and oxidation potential (E O ) difference (ΔE OE–O ); (2) the coating layer having not less than 45wt% of the tetravalent cobalt compound slows down the oxygen evolution reaction rate of the positive electrode material at high temperature; (3) the coating layer having not less than 45wt% of the tetravalent cobalt compound reduces the oxidation potential (E O ) and reduction potential (E R ) difference (ΔE O–R ) to increase the reversibility of the reaction, thereby reducing capacity decay; (4) the coating layer having not less than 45 wt% of the tetravalent cobalt compound contains more micropores to adsorb water, thereby reducing the amount of free water.
[0019] In a second aspect, the present invention provides a method for preparing the positive electrode material, the method comprising the following steps:
[0020] A precursor preparation process using a coprecipitation method, preparing a first solution containing M ions (M is one of Ca, Mg, and Zn), cobalt ions, nickel ions, and ammonium ions, preparing a first alkaline solution containing hydroxide ions, uniformly mixing the first alkaline solution and the first solution, then collecting a precipitate, washing the precipitate and drying it at high temperature to obtain a precursor;
[0021] A coating process, comprising preparing a second alkaline solution containing ammonium ions, preparing a second solution containing cobalt ions, dispersing the precursor in the second solution to form a first suspension, then adding the second alkaline solution to the first suspension under stirring, collecting a precipitate, washing the precipitate and drying it at high temperature to obtain a granular material having a coating layer, wherein the coating layer comprises α-Co(OH)2;
[0022] In the oxidation process, a sodium hypochlorite solution is prepared, and the granular material is dispersed in water to form a second suspension. Then, the sodium hypochlorite solution is added to the second suspension while maintaining a constant temperature and stirring, and the precipitate is collected. The precipitate is washed and dried to obtain the positive electrode material.
[0023] In the process of preparing the precursor, the first solution and the first alkaline solution are mixed, so that low concentrations of M ions, cobalt ions and high concentrations of nickel ions are converted into hydroxides under alkaline conditions to be enriched, and there are related surface compounds produced by the complex reaction of ammonium ions, water molecules and surface hydroxide ions on the surface. The precipitation rates of M ions, cobalt and nickel are similar. Further, the first alkaline solution is a solution obtained by strong alkali configuration, such as sodium hydroxide solution, potassium hydroxide solution, which is used to precipitate the metal ions in the first solution. From the perspective of reducing costs, the metal ions in the first solution are preferably derived from sulfates (cobalt ions are derived from cobalt sulfate, M ions are derived from sulfuric acid M, and nickel ions are derived from nickel sulfate), and ammonium ions are preferably derived from ammonium sulfate. If the metal ions in the first solution come from chlorides, a small amount of chloride ions will remain in the precursor, and the presence of chloride ions will ultimately be detrimental to the electrochemical properties of the positive electrode material. The precipitate collected after the first alkaline solution and the first solution are mixed is a hydroxide precipitate enriched with M, cobalt and nickel, and its main component is nickel hydroxide. The nickel hydroxide in the prepared precursor has high crystallinity, and thus can significantly inhibit the oxidant from oxidizing the nickel hydroxide in the oxidation process.
[0024] Furthermore, if the M ion is a Zn ion, during the mixing process of the first solution and the first alkaline solution, the speed at which the first alkaline solution is added to the first solution and the pH value of the final mixed solution are controlled to inhibit the precipitated zinc hydroxide from dissolving in a strong base to form zincate or the zinc hydroxide from reacting with ammonia water to form zinc ammine complex ions.
[0025] Furthermore, the prepared precursor can give full play to the function of doping ions to improve the solid-phase electronic conductivity, solid-phase structural stability and solid-phase proton conduction characteristics of nickel hydroxide. The positive electrode material prepared by the method provided by the present invention can significantly improve the reaction performance of nickel hydroxide in the positive electrode material, so that the charging reaction of the material can be completed before the oxygen evolution side reaction occurs, effectively avoiding the occurrence of adverse results such as reduced charging coulomb efficiency, increased battery internal pressure and severe battery heating caused by the oxygen evolution reaction, making the battery safer and more energy efficient.
[0026] In the coating process, the uniformity and adhesion of the coating with α-Co(OH)2 as the main component can be stably ensured. The second alkaline solution is supplied to the first suspension, and the second alkaline solution is highly dispersed under mechanical stirring, so that the second alkaline solution can be quickly and evenly mixed with the first suspension, achieving the purpose of evenly and slowly adjusting the pH value of the mixed solution, and also allowing the precipitation reaction of cobalt hydroxide produced by cobalt ions to be very uniformly carried out on the three-dimensional spatial scale of the solution to form nano cobalt hydroxide, which not only effectively controls the size of cobalt hydroxide particles and the uniformity of cobalt hydroxide attachment to the surface of the precursor (nickel hydroxide doped with M and cobalt), but also is very conducive to the rapid formation of a crystal structure of cobalt hydroxide.
[0027] It was unexpectedly discovered that the surface-coated α-Co(OH)2 obtained in the coating process exhibited a controlled microcrystalline morphology, which would make the subsequent oxidation process easier to control, faster in oxidation speed, and more thorough in oxidation.
[0028] Furthermore, the cobalt ions in the second solution come from a cobalt salt, and the cobalt salt is not particularly limited as long as it can generate a water-soluble cobalt salt compound of α-Co(OH)2 according to pH control. Specifically, cobalt sulfate and cobalt chloride are preferred, and cobalt sulfate without halogen pollution is more preferred.
[0029] Furthermore, in the process of supplying the second alkaline solution to the first suspension, nano-scale cobalt hydroxide primary particles are first generated in the solution phase, and the composite material particles formed after the cobalt hydroxide particles attach to the surface of the precursor are secondary nanoparticles. By controlling the speed at which the second alkaline solution is added to the first suspension, the purpose of slowly and evenly adjusting the pH value in the entire reaction solution is achieved, so that the cobalt hydroxide is evenly coated on the surface of the precursor, and it is ensured that the generated cobalt hydroxide mainly includes α-Co(OH)2.
[0030] In the oxidation process, the α-Co(OH)2 on the surface of the granular material is oxidized by using a sodium hypochlorite solution to obtain a cobalt compound with a higher valence state, which can significantly improve the electronic conductivity of the positive electrode material, and the coating of the obtained positive electrode material is uniform and the adhesion of the coating layer is better. The content of the tetravalent cobalt compound in the coating layer of the obtained positive electrode material is indirectly controlled by controlling the content of the sodium hypochlorite in the sodium hypochlorite solution and the speed at which the sodium hypochlorite solution is added to the second suspension.
[0031] Furthermore, the coating layer of the positive electrode material prepared by the method provided by the present invention has a porous structure, so that the positive electrode material has fast solid-phase proton conduction characteristics during the charge and discharge process, and the liquid phase in the solid porous positive electrode material has fast ion conduction ability, so that the positive electrode material has both low ohmic drop and low reaction impedance during high-rate charge and discharge, and can meet the requirements of high-rate fast reaction. The alkaline secondary battery containing the positive electrode material has a porous structure, so that the coating layer contains more micropores to absorb water, thereby reducing the amount of free water in the electrolyte of the alkaline secondary battery, which is beneficial to suppressing the capacity decay problem of the alkaline secondary battery at high temperature.
[0032] The inventors have found that the content of the tetravalent cobalt compound in the coating layer of the positive electrode material prepared by the above method is not less than 45 wt %.
[0033] The preparation method provided by the present invention can be implemented in a continuous manner to improve production efficiency. However, in order to achieve uniform coating of nickel hydroxide, it is preferably implemented in an intermittent manner.
[0034] In a third aspect, the present invention provides an alkaline secondary battery, wherein the positive electrode active material of the alkaline secondary battery includes the positive electrode material. The positive electrode material has high conductivity and stability, and is therefore suitable for use as a positive electrode active material of an alkaline secondary battery used as a power source for electric vehicles or hybrid vehicles requiring high output characteristics, and the positive electrode material improves utilization by improving conductivity, and is therefore also extremely effective as a positive electrode active material of an alkaline secondary battery used as a power source for portable electronic devices requiring high capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The accompanying drawings further illustrate the present invention, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention.
[0036] Figure 1 This is the SEM image of FTC4 of Example 1.
[0037] Figure 2 This is the SEM image of SJ18P in Example 1.
[0038] Figure 3 This is the EDS layered image of FTC4 in Example 1.
[0039] Figure 4 SEM images of FTC4, B04-40-AB and B05-250-A at a magnification of 10.00K.
[0040] Figure 5 SEM images of FTC4, B04-40-AB and B05-250-A at a magnification of 70.00K.
[0041] Figure 6 XPS analysis valence state diagram of FTC4, B04-40-AB, B05-250-A, SJ18P, SJ18NP and SJ18.
[0042] Figure 7(a) and Figure 7(b) are cyclic voltammetry test graphs.
[0043] Figure 8 Schematic diagram of the discharge capacity of a half-cell at room temperature. DETAILED DESCRIPTION
[0044] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0045] The inventors studied the existing technical solutions for preparing nickel hydroxide positive electrode materials and obtained the following knowledge:
[0046] 1. The existing method for preparing nickel hydroxide is mainly a liquid phase deposition method, in which nickel hydroxide is deposited by adding alkali to a nickel-containing solution. If doping is performed, a mixed solution of nickel ions and doping ions is used for a co-precipitation reaction. However, the method of adding alkali solution or continuously flowing alkali solution into the reaction solution used in the deposition process is likely to cause the local alkali concentration in the solution to be too high, resulting in the formation of uneven amorphous agglomerate particles due to the local deposition speed being too fast. Such agglomerates require subsequent high temperature and long-term aging processes to explain the formation of a β-type crystal structure. For the preparation of doped nickel hydroxide materials, the local excessively high alkali concentration is also likely to cause uneven deposition distribution of the doping elements, so that the functional characteristics of doping, such as stable crystal structure, improved solid-phase electronic conductivity and improved solid-phase proton conductivity, cannot be brought into play. The prepared nickel hydroxide material has the problems of large particles, poor electronic conductivity and low solid-phase proton conductivity, which makes the actual utilization efficiency of the material low, and the high-rate charge and discharge performance is poor, which seriously restricts its application in high-power alkaline secondary batteries;
[0047] 2. In the process of preparing a cobalt hydroxide coating layer on the surface of nickel hydroxide by the existing coprecipitation method, when the cobalt ion concentration increases sharply and exceeds the critical supersaturation in the pH region of the suspension where the cobalt ions exist, cobalt hydroxide will precipitate alone in the water even if there are no nickel hydroxide particles nearby. However, when the pH value of the above suspension is low, specifically, when the pH is less than 8, the precipitation rate of cobalt hydroxide slows down. Therefore, even if the cobalt ion concentration exceeds the critical supersaturation, cobalt hydroxide may precipitate alone. On the one hand, when the pH value of the suspension where the cobalt ions exist is greater than 8, since the critical supersaturation of the cobalt ion concentration decreases, if the cobalt ion concentration is increased, it will easily exceed the critical supersaturation. As a result, the cobalt hydroxide does not adhere to the surface of the nickel hydroxide particles but precipitates alone. The cobalt hydroxide precipitated alone adheres to the surface of the nickel hydroxide particles, resulting in poor uniformity;
[0048] 3. The surface of spherical nickel hydroxide is coated with a divalent cobalt compound (mainly cobalt hydroxide) and then oxidized using the existing technology, so that the divalent cobalt compound of the coating layer is oxidized to form the existing higher-valent cobalt oxyhydroxyl. The main component of the obtained coating layer is β-CoOOH (+3 valence of cobalt in β-CoOOH). When using this positive electrode active material, alkaline secondary batteries often have the problem of irrecoverable positive electrode capacity under high current discharge, deep discharge, short circuit and other conditions. The main reason is that when the nickel hydroxide is deeply discharged, the conductive network material β-CoOOH on the surface of the nickel hydroxide will also undergo a partial reduction reaction. The reduced divalent cobalt will form a cobalt complex ion in the battery electrolyte, causing the dissolution of cobalt, thereby causing the incompleteness of the β-CoOOH conductive network;
[0049] 4. After the surface of the spherical nickel hydroxide is coated with a divalent cobalt compound (mainly cobalt hydroxide), it is oxidized using existing technology. In order to oxidize the divalent cobalt compound in the coating layer to form γ-CoOOH with a valence higher than +3 (the valence of cobalt in γ-hydroxy cobalt oxide has two valences, +3 and +4, and the average valence is greater than +3, and its theoretical valence is as high as +3.67), it is necessary to use oxygen under alkaline conditions to oxidize the cobalt hydroxide layer coated on the surface of the nickel hydroxide. However, the direct oxidation reaction of cobalt hydroxide will vary greatly depending on the concentration of the surrounding alkaline components, the slight moisture of the particles, the temperature of the particles themselves during treatment, the surrounding humidity and oxygen concentration, and there are complex reaction trajectories, resulting in the cobalt in part of the cobalt coating layer not being fully oxidized. In particular, the water generated during the reaction will cause the cobalt-coated spherical nickel to be easily agglomerated during oxidation, and in the subsequent washing process, the cobalt coating layer will be damaged due to adhesion;
[0050] 5. The oxidation reaction of the cobalt hydroxide layer coated on the surface of nickel hydroxide is not only affected by the control of the oxidation process; it is also affected by the technical control when the cobalt hydroxide is formed, especially closely related to the surface crystal state (microcrystalline morphology) of the coating layer. In other words, the microcrystalline morphology of cobalt hydroxide has a direct impact on the composition of the coating layer finally oxidized, the uniformity and integrity of the coating layer, and the tightness of the bonding with the substrate, which in turn affects the high current discharge performance, over-discharge recovery performance and cycle life of the positive electrode material.
[0051] 6. In the existing technical solution, in the process of using oxygen as an oxidant to oxidize the surface-coated cobalt hydroxide layer to obtain γ-CoOOH, there is a process of redissolution and recrystallization aggregation, which specifically includes the following reaction formula:
[0052] Co(OH)2+OH - →HCoO2 - +H2O(dissolution reaction)
[0053] HCoO2-+1 / 2H2O+1 / 4O2→CoOOH+OH - (Oxidation precipitation reaction)
[0054] If the recrystallized and aggregated γ-CoOOH does not occur on the surface of the nickel hydroxide particles, but is free outside the spherical nickel hydroxide particles, it will directly affect the amount of cobalt coating on the surface of the nickel hydroxide particles, and further affect the uniformity of the conductive network, the integrity of the particles and the conductivity.
[0055] 6. In the existing technical solutions, other oxidants such as sodium hypochlorite, persulfate, etc. are used to replace oxygen to oxidize cobalt hydroxide into cobalt oxyhydroxy. However, these oxidants are more likely to react with nickel hydroxide than oxygen to generate relatively unstable nickel hydroxide oxide. Therefore, the adhesion of the cobalt hydroxide coating becomes unstable.
[0056] The improvements of the technical solution provided by the present invention compared with the above-mentioned knowledge will now be described with reference to specific embodiments.
[0057] [Example 1]
[0058] This embodiment provides a positive electrode material, which includes a core material and a coating layer coated on the surface of the core material. The core material includes nickel hydroxide, and the coating layer includes a tetravalent cobalt compound, and based on the weight of the coating layer, the content of the tetravalent cobalt compound is 67wt%.
[0059] The method for preparing the positive electrode material provided in this embodiment comprises the following steps:
[0060] S100, dissolve 3.50 g of ZnSO4·7H2O, 43.00 g of NiSO4·6H2O, 0.95 g of CoSO4·7H2O and 5.00 g of (NH4)2SO4 in 250 mL of deionized water to obtain a first solution, prepare 1N NaOH solution as a first alkaline solution, add the first alkaline solution to the first solution at a rate of 3 mL / min, adjust the pH of the mixed solution to 12 and keep it at room temperature for 24 h (if necessary, use 10 N NaOH to adjust the pH value), collect the precipitate, wash the precipitate and dry it at 80 ° C for 12 h to obtain a precursor, marked as SJ18P;
[0061] S200, dissolve 10g of (NH4)2SO4 in 60mL of deionized water to obtain solution A, fully mix 100mL of NH3·H2O with 100mL of deionized water to obtain solution B, mix solution A and solution B to obtain a second alkaline solution; dissolve 37.80g of CoSO4·7H2O in 1000mL of deionized water to obtain a second solution, put about 250g of SJ18P into the second solution and stir and disperse for 15min to form a first suspension; while maintaining the stirring state (stirring The second alkaline solution was added to the first suspension at a speed of 1.0 mL / min under a stirring speed of 460 rpm, and the pH value of the mixed solution was controlled to be within the range of 8.1±0.1 when the color of the mixed solution changed from green to blue-green, and the total amount of the second alkaline solution added was controlled to be about 47 mL; after aging for 60 min, stirring was stopped, and the precipitate was collected, and the precipitate was washed and dried at about 55° C. for 12 h to obtain a granular material having α-Co(OH)2 as a coating layer, which was marked as SJ18NP;
[0062] S300, about 3.50g of SJ18NP was put into 200mL of deionized water, and a second suspension was formed while being heated in a water bath (the water bath temperature was about 55°C) and stirred (the stirring speed was controlled at 250rpm), and the second suspension was kept at a constant temperature of about 55°C; 1.3mL of NaClO solution (the content of NaClO was 4.5wt%) was diluted with 9mL of deionized water, and then added dropwise to the second suspension, and the addition process took about 3min; then stirring was maintained at a stirring speed of 250rpm for 1h, the precipitate was collected, the precipitate was washed and dried at about 55°C for 12h, and the positive electrode material was obtained, marked as FTC4, with a yield of about 3.5g.
[0063] The SEM image of FTC4 is as follows Figure 1 As shown, the SEM image of SJ18P is Figure 2 As shown, according to Figure 1 and Figure 2By comparison, it can be judged that the coating layer completely covers the surface of SJ18P, and no surface structure of SJ18P can be seen on the prepared positive electrode material FTC4. The EDS layered image of FTC4 is shown in Figure 3 As shown, the cobalt element in the coating layer is evenly distributed. Therefore, when FTC4 is used as the positive electrode active material of the battery, the uniform presence of the conductive cobalt compound can fully form a conductive network between the positive electrode material particles and improve the utilization efficiency of the positive electrode.
[0064] In step S100, by controlling the addition rate of the first alkaline solution, the local alkali concentration in the mixed solution is avoided to be too high, and by limiting the addition rate of the first alkaline solution to limit the deposition rate, the precursor particles with uniform deposition distribution are formed, and the prepared precursor particles are uniform in size. By controlling the composition of metal ions in the first solution and adjusting and keeping the pH of the mixed solution constant to 12, the nickel hydroxide in the obtained precursor is a β-type crystal structure and a stable crystal structure is obtained by doping zinc and cobalt. The precursor can be used as a core material and can significantly inhibit oxidation by sodium hypochlorite in the oxidation process.
[0065] In step S200, during the process of adding the second alkaline solution to the first suspension, cobalt exists in an ionic state in the region with low pH value of the mixed solution, but cobalt hydroxide begins to precipitate gradually as the pH value of the mixed solution increases. At this time, if nickel hydroxide particles exist nearby, cobalt hydroxide is precipitated on the surface of the nickel hydroxide particles which are more stable in energy. Continuous stirring of the mixed solution can prevent the mixed solution from having a state where the cobalt ion concentration is extremely high, and controlling the addition rate and total amount of the second alkaline solution can inhibit the formation of a high pH region in the mixed solution. The precipitation rate of cobalt hydroxide can be adjusted by controlling the pH value of the mixed solution, and it is found that when the pH value of the mixed solution is within the range of 8.1±0.1, the presence of precursor particles will inhibit the precipitation of cobalt hydroxide alone, and α-Co(OH)2 with high adhesion will be uniformly precipitated on the surface of the precursor particles, and the microcrystalline morphology of the precipitated cobalt hydroxide is affected by the synergistic effect of the pH range control and the precursor particles.
[0066] In step S300, the second suspension is kept at a constant temperature of about 55°C and a sodium hypochlorite solution is added. The reason is that when the temperature is less than about 50°C, the oxidation reaction rate decreases; when it exceeds 60°C, the oxidation reaction rate is too fast, so the α-Co(OH)2 of the coating layer is unevenly oxidized. In addition, the temperature of the second suspension is preferably kept at a fixed value within a temperature range of 55°C, and the variation range is ±1°C. When the temperature exceeds the above variation range, the content of the tetravalent cobalt compound in the coating layer of the formed positive electrode material will change, so the characteristics when used in the battery may be unstable. Sodium hypochlorite is used as an oxidant to oxidize α-Co(OH)2 into a high-valent cobalt compound. Compared with oxygen, sodium hypochlorite is a high-valent oxidant, and based on the special structure of the precursor coating α-Co(OH)2, sodium hypochlorite can oxidize α-Co(OH)2 into a coating layer with 67wt% of tetravalent cobalt compound. By controlling the addition rate of the sodium hypochlorite solution and combining it with subsequent stirring, the oxidation of α-Co(OH)2 becomes sufficient.
[0067] The coating layer of the positive electrode material obtained in this embodiment may contain at least one of γ-CoOOH (the cobalt contained in it is not in the +4 valence state) and β-CoOOH in addition to the tetravalent cobalt compound.
[0068] [Example 2]
[0069] This embodiment provides a positive electrode material, which includes a core material and a coating layer coated on the surface of the core material. The core material includes nickel hydroxide, and the coating layer includes a tetravalent cobalt compound, and based on the weight of the coating layer, the content of the tetravalent cobalt compound is 76wt%.
[0070] The method for preparing the positive electrode material provided in this embodiment comprises the following steps:
[0071] S100, the same as step S100 in Example 1, preparing SJ18P;
[0072] S200, the same as step S200 in Example 1, preparing SJ18NP;
[0073] S300, about 40g of SJ18NP was put into 1200mL of deionized water, and a second suspension was formed while being heated in a water bath (the water bath temperature was about 25°C) and stirred (the stirring speed was controlled at 280rpm), and the second suspension was kept at a constant temperature of about 25°C; 1.8mL of NaClO solution (the content of NaClO was 18wt%) was diluted with 20mL of deionized water, and then added dropwise to the second suspension, and the addition process took about 20min; then stirring was maintained at a stirring speed of 280rpm for 1h, the precipitate was collected, the precipitate was washed and dried at about 55°C for 12h, and the positive electrode material was obtained, marked as B04-40-AB, with a yield of about 40g.
[0074] [Example 3]
[0075] This embodiment provides a positive electrode material, which includes a core material and a coating layer coated on the surface of the core material. The core material includes nickel hydroxide, and the coating layer includes a tetravalent cobalt compound, and based on the weight of the coating layer, the content of the tetravalent cobalt compound is 74wt%.
[0076] The method for preparing the positive electrode material provided in this embodiment comprises the following steps:
[0077] S100, the same as step S100 in Example 1, preparing SJ18P;
[0078] S200, the same as step S200 in Example 1, preparing SJ18NP;
[0079] S300, about 250g of SJ18NP was put into 3000mL of deionized water, and a second suspension was formed while being heated in a water bath (the water bath temperature was about 25°C) and stirred (the stirring speed was controlled at 260rpm), and the second suspension was kept at a constant temperature of about 25°C; 10mL of NaClO solution (the content of NaClO was 18wt%) was diluted with 100mL of deionized water, and then added dropwise to the second suspension, and the addition process took about 20min; then stirring was maintained at a stirring speed of 260rpm for 1h, the precipitate was collected, the precipitate was washed and dried at about 55°C for 12h, and the positive electrode material was obtained, marked as B05-250-A, with a yield of about 250g.
[0080] Figure 4 and Figure 5 The SEM images of FTC4, B04-40-AB and B05-250-A at different magnifications are shown in Figure 2. Figure 4 and Figure 5It can be judged that the coating layers of the three positive electrode materials completely cover the surface of SJ18P, and the coating layers of the three positive electrode materials are all porous structures, which makes the coating layers contain more micropores to absorb water, thereby reducing the amount of free water in the electrolyte of the alkaline secondary battery, which is beneficial to inhibiting the capacity attenuation problem of alkaline secondary batteries at high temperatures.
[0081] [Comparative Example 1]
[0082] This embodiment provides a positive electrode material, and the preparation method of the positive electrode material comprises the following steps:
[0083] S100, about 10 g of SJ18NP and about 10 mL of 10 N NaOH solution were mixed to obtain a slurry;
[0084] S200, blowing air into the slurry at a flow rate of 3.5 L / min for 4 hours, thereby oxidizing the precipitated cobalt hydroxide into cobalt oxyhydroxide. At this time, the total amount of oxygen supplied relative to the molar amount of cobalt in the coating is 52.0 L / mol;
[0085] S300, solid-liquid separation was performed using a filter press, the recovered powder was washed with water, and filtered again, and then the obtained powder was dried at 120° C. for 20 hours using a vacuum dryer to obtain a positive electrode material, which was labeled as SJ18.
[0086] XPS analysis was performed on the coating layers of the positive electrode materials provided in Examples 1-3 and the positive electrode material provided in Comparative Example 1, and the obtained results are shown in Table 1.
[0087] Table 1
[0088]
[0089] According to the results in Table 1, it can be judged that the content of tetravalent cobalt compound in the coating layer obtained by oxidizing the nickel hydroxide particle material coated with cobalt hydroxide using the existing technical solution is 24wt%, which is much lower than 45wt%. Therefore, the positive electrode material prepared by the method provided by the present invention can obtain higher conductivity and better stability.
[0090] XPS analysis of the coating layers of FTC4, B04-40-AB, B05-250-A, SJ18P, SJ18NP and SJ18 showed the following results: Figure 6As shown in the figure (B05-250-A material was subjected to two XPS analysis states, and the second XPS analysis state was marked as B05-250-A-2 for distinction), the Co 2p3 / 2 peak near 780.5 eV can be decomposed into two fitting peaks, 780.03 eV and 781.19 eV, respectively. The peak with a binding energy of 780.03 eV can be attributed to trivalent cobalt, while the peak at 781.19 eV can be attributed to tetravalent cobalt, Co 4+ / Co 3+ The ratio can be estimated by integrating the corresponding peak areas. Figure 6 It can be judged that the method provided by the present invention can obtain 4+ / Co 3+ The ratio of the coating layer.
[0091] FTC4, B04-40-AB, B05-250-A and SJ18 are used as active materials to prepare working electrodes. This process can be achieved by any existing technology. A three-electrode system (including Hg / HgO as a reference electrode, nickel foam as a comparison electrode and the working electrode, and a 30wt% KOH solution as the electrolyte) is used, and a Maccor 4000 series is used to perform a cyclic voltammetry test on the working electrode at 80°C. The results are shown in Figures 7(a) and 7(b). As shown in Figures 7(a) and 7(b): The difference between the oxidation potential and the reduction potential of the SJ18 material at 80°C is ΔE OE–O =18mV; ΔE is the difference between the oxidation potential and the reduction potential of FTC4 material at 80°C OE–O =20mV; ΔE is the difference between the oxidation potential and the reduction potential of the B04-40-AB material at 80°C OE–O =20mV; ΔE is the difference between the oxidation potential and the reduction potential of B05-250-A material at 80°C OE–O =21mV. ΔE OE–O The larger the value, the better the stability of the material at high temperature.
[0092] The same mass of FTC4, B04-40-AB, B05-250-A and SJ18 were used as positive electrode active materials to prepare half-cells with the same specifications. This process can be achieved by any existing technology. After the half-cell was started (charged at a rate of 57.8mAh / g for 6 hours; discharged at a rate of 57.8mAh / g until the cut-off voltage of 1V; repeated charging and discharging until the positive electrode was fully started and reached its maximum capacity), its discharge capacity (cut-off voltage of 1V) at room temperature (25-30°C) was tested. The results are as follows: Figure 8 As shown. Figure 8As shown, the positive electrode material provided by the present invention has a higher capacity, because the coating layer of the positive electrode material has a high content of tetravalent cobalt compound, which makes the utilization rate of Ni(OH)2 of the core material higher.
[0093] The same mass of B05-250-A and SJ18 were used as positive electrode active materials to prepare full batteries of the same specifications of 500mAh (battery model is AAA battery). The negative electrode material of the full battery adopts hydrogen storage material, the positive electrode of the full battery is a positive electrode active material, cobalt oxide (CoO) and ytterbium trioxide (Yb2O3) configured at a mass ratio of 98:1:1, and the electrolyte of the full battery is an alkaline solution including sodium hydroxide (NaOH) and lithium hydroxide (LiOH). After the full battery is activated, the capacity (i.e., initial capacity) is calibrated at room temperature, and then the two ends of the fully charged full battery are connected to 2 ohm internal resistance and placed in a high-temperature oven at 60°C for 14 days of high-temperature short-circuit test. Finally, the full battery is placed at room temperature to discharge the remaining power and then charged and the capacity is measured (i.e., capacity after high-temperature short-circuit test). Capacity recovery rate = (capacity after high-temperature short-circuit test) / (initial capacity), the higher the capacity recovery rate, the better. The test results are shown in Table 2, which indicates that the positive electrode material provided by the present invention provides a higher power recovery, and the full battery using the positive electrode material provided by the present invention can significantly improve the high temperature performance.
[0094] Table 2
[0095] Positive electrode active materials for full batteries After 14 days of short circuit test at 60℃, the power is restored B05-250-A 66% SJ18 53%
[0096] Since the positive electrode material of the present invention has high conductivity, it has high utilization rate as a positive electrode active material of an alkaline secondary battery and is suitable as a power source for portable electronic devices requiring high capacity. In addition, it is also suitable for electric vehicles requiring high output characteristics.
[0097] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0098] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a positive electrode material, characterized in that: The positive electrode material comprises a core material and a coating layer coated on the surface of the core material, wherein the core material is a general formula Ni 1-x-y Co x N y Nickel hydroxide represented by (OH)2, x is 0.005-1, y is 0.005-1, N is one of calcium, magnesium and zinc, the coating layer includes a tetravalent cobalt compound, and the content of the tetravalent cobalt compound is 67-76wt% based on the weight of the coating layer; The preparation method comprises the following steps: A precursor preparation process using a coprecipitation method, preparing a first solution containing M ions, cobalt ions, nickel ions and ammonium ions, wherein M is one of calcium, magnesium and zinc, preparing a first alkaline solution containing hydroxide ions, uniformly mixing the first alkaline solution and the first solution, then collecting a precipitate, washing the precipitate and drying it at high temperature to obtain a precursor; A coating process, comprising preparing a second alkaline solution containing ammonium ions, preparing a second solution containing cobalt ions, dispersing the precursor in the second solution to form a first suspension, then adding the second alkaline solution to the first suspension under stirring, collecting a precipitate, washing the precipitate and drying it at high temperature to obtain a granular material having a coating layer, wherein the coating layer comprises α-Co(OH)2; In the oxidation process, a sodium hypochlorite solution is prepared, and the granular material is dispersed in water to form a second suspension. Then, the sodium hypochlorite solution is added to the second suspension while maintaining a constant temperature and stirring, and the precipitate is collected. The precipitate is washed and dried to obtain the positive electrode material.
2. The method according to claim 1, characterized in that The M ion is a zinc ion.
3. The method according to claim 2, characterized in that The cobalt ions come from cobalt sulfate, the zinc ions come from zinc sulfate, the nickel ions come from nickel sulfate, and the ammonium ions come from ammonium sulfate.
4. The method according to claim 3, characterized in that In the step of preparing the precursor by the coprecipitation method, the first alkaline solution is added to the first solution at a rate of 3 mL / min, and the pH of the mixed solution formed by the first alkaline solution and the first solution is adjusted to 12.
5. The method according to claim 4, characterized in that In the coating process, the second alkaline solution is added to the first suspension at a rate of 1.0 mL / min, and the pH value of the mixed solution is controlled within the range of 8.0-8.2 after the color of the mixed solution formed by the second alkaline solution and the first suspension changes from green to blue-green.
6. An alkaline secondary battery, characterized in that: The positive electrode active material of the alkaline secondary battery comprises a positive electrode material prepared by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Coated Nickel Hydroxide Powder as Cathode Active Material for Alkaline Secondary Battery and Method for Producing the Same
US20120276453A1
Positive electrode active material for alkaline secondary battery and alkaline secondary battery including the positive electrode active material
US20170237066A1